Reduced longitudinal change in 18F‐flortaucipir PET is associated with clinical phenotype in atypical Alzheimer's disease. (31st December 2021) - Phillips, Jeffrey S; Nitchie, Frederick J.; Da Re, Fulvio; Olm, Christopher A; Cook, Philip; McMillan, Corey T; Irwin, David J.; Gee, James C.; Dubroff, Jacob G.; Grossman, Murray; Nasrallah, Ilya M.
Abstract: Background: Longitudinal positron emission tomography (PET) studies of tau accumulation in Alzheimer's disease (AD) have noted reduced increases or frank decreases in tau signal. It is unclear whether these reductions reflect measurement/processing error or biological changes in advanced neurodegeneration. Method: We assessed regional and interindividual variation in rates of longitudinal change on 18 F‐flortaucipir PET imaging in 24 amyloid‐β+ patients with atypical, early‐onset amnestic or non‐amnestic AD and 117 amyloid‐β+ participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study. Result: In atypical AD, 18 F‐flortaucipir uptake appeared to slow or decline over time in areas with high baseline signal and older individuals with greater cognitive impairment. In secondary analyses, these effects were not explained by regression to the mean or atrophy. Among ADNI participants, longitudinal change was reduced in early Braak stage regions relative to late‐stage neocortical areas, demonstrating partial generalization of findings from atypical AD. Conclusion: Results suggested that radioligand uptake may plateau or decline in advanced neurodegeneration. Further research is warranted to investigate whether results generalize to other tau‐binding radioligands and to typical, later‐onset AD.